Sutrah dalam Shalat: Pemahaman Kaum Feminis terhadap Hadis yang Menyetarakan Perempuan dengan Hewan - Ridwan, Muhd (Jurnal Riset Agama, 2023)
This study aims to discuss the hadith about understanding the sutrah in prayer. This research is a qualitative type through literature study using the method of hadith analysis. The results of the study found that the sutrah or barrier in prayer, its form does not have to be in accordance with what has been mentioned in the hadith, as long as the object can prevent someone from passing in front of the person who is praying. Sutrah is not an obligation that becomes a valid condition of prayer. The feminist criticism of the hadith that is considered to equalize women with animals is very unfounded, because it is only seen literally but does not study the meaning of the hadith.